COVID-19 and Sovereign Debt: The case of SADC - Bradlow, Daniel D.; Masamba, Magalie L. (Pretoria University Law Press (PULP), 2022)
This multi-disciplinary publication focuses on the issue of African sovereign debt management and renegotiation/ restructuring, with a particular concentration on the countries that are members of the Southern Africa Development Community (SADC). It contains a series of essays that were initially presented in several workshops held at the height of the pandemic, in 2020. These essays seek to both understand the debt challenges facing these countries and to offer some policy-oriented suggestions on how they can more effectively address these. They include contributions by global and regional scholars who are seasoned experts and newer researchers and discuss the complexities on debt management and restructuring within the context of the global COVID-19 pandemic. In particular, this presented an opportunity for junior researchers from the region to contribute to international discussions on a topic in which the views of young Africans are not heard as often or as clearly as they should be, especially given the importance of the topic to Africa and its future. Further, this book is expected to stimulate debate among academics, activists, policy makers and practitioners on how SADC should manage its debt.